KOMPOSISI DAN KEANEKARAGAMAN BENTOS DI SUNGAI BATANG KUANTAN KABUPATEN SIJUNJUNG - Junita, Reren Maria; Nurhadi, Nurhadi; Nursyahra, Nursyahra (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Influence of benthos have be affected environment in water factor, biological factor although physics and chemistry water. Benthos compositions make be indicator in thr water quality. Study to know compositions and diversity benthos in Batang Kuantan River. Research until Maret 2013 with Survey Descriptive method. It was do effect in gold mining waste. Total of 13 genus of the benthos the belonging 3 classis, 6 ordo, and 12 famili. The highest of density showedin the station I (1437,77 individu/m2), and the lowest density showed in the station II (177,34 individu/m2). The highest frequency showed in the stasion I (8,00) and the lowest frequency showed in the station II (1,66). Indeks Diversity the benthos turn of 0,5625-2,0358, thus Batang Kuantan River heavily polluted category. Physics and chemistry factor of the Batang Kuantan River still suitable for life the benthos.Â